Experimental study on wave dampening ability of floating breakwaters - Teh, H.M. (2013)
Floating breakwaters are gaining increased importance in many marine and coastal applications. Various researches have been conducted to optimize the design of floating breakwaters so as to attain greater hydraulic efficiency and functional value. In this research, two floating breakwaters of different design were developed with the aim to reduce wave energy mainly by reflection and energy loss. Both breakwaters (Model 1 and Model 2) possessed a rectangular body with a pair of arms at the top and a pair of legs at the bottom. The legs of Model 1 and Model 2 were upright and 45o slanted, respectively. Hydraulic performances of these breakwaters subjected to unidirectional monochromatic waves were assessed by the means of physical modeling, and were subsequently quantified by the energy coefficients, namely the coefficients of wave transmission and reflection, and energy loss. The major experimental finding for this study is that Model 1 is a dissipative-type breakwater and Model 2 is a reflective-type breakwater. Both models are efficient wave attenuators and are capable of suppressing the incident wave heights up to 80 in shallow water condition. Â© (2013) Trans Tech Publications, Switzerland.